Cryosurgery combined with Iodine-125 seed implantation in the treatment of unresectable lung cancer - Hongta ZHOU; Lizhi NIU; Liang ZHOU; Feng MU; Changming ZHANG; Bing LIANG; Daming YANG; Kecheng XU (Chinese Journal of Lung Cancer, 2008)
Background and objective As many lung cancer patients lose surgical possibility, it is important to explore new treatments to improve prognosis. The study is to observe adverse reactions and therapeutic effects of cryosurgery combined iodine-125 seeds implantation in treating advanced lung cancer patients. Methods One hundredforty unresectable pulmonary cancer patients received percutaneous cryosurgery and iodine-125 implantation under CT guidance. Patients were followed-up 1 year, with CT scan, therapeutic effect, complications and survival time monitoriy. Results The one hundred forty patients successfully received cryosurgery combined with iodine-125 seed implantation and one-year follow-up. The patients with 6 m posttreatment had complete remission (CR) of 93.4%, partial remission(PR) of 70.1%, stable disease (SD) of 7.4%, and progressive disease (PD) of 5.7%. The half-year and one-year survival rates were 94.3% and 65.7% respectively. The average KPS was improved from 66.9 to 76.3. Conclusion Cryosurgery combined with iodine-125 seed implantation is effective in treating unresectable lung cancer, providing a promising treatment protocol for unresectable lung cancer patients.